Effect of sodium hypochlorite in ground fluorotic enamel : shear bond strength and surface analysis = Efecto del hipoclorito de sodio en esmalte fluorótico tallado : resistencia adhesiva al cizallamiento y análisis de la superficie - Roque Márquez, José Gilberto; Zavala Alonso, Norma Verónica; Patiño Marín, Nuria; Martínez Castañón, Gabriel Alejandro (2021)
Evaluate the effect on the shear bond strength (SBS) of 5% NaOCl applied after acid etching on ground anterior teeth with fluorosis and analyze the surface with scanning electron microscopy (SEM), also compare fluorotic and healthy ground enamel by atomic force microscopy (AFM) and Vickers microhardness (VM). For the SBS test 30 anterior teeth with moderate and severe fluorosis according Dean index were selected by an examiner previously calibrated with an expert in fluorosis by using the intraclass correlation coefficient (ICC). With the help of a calibrated high speed diamond bur for veneer preparation and a parallel chamfer high speed diamond bur the vestibular face was prepared with a uniform reduction of .3 mm under water cooling. In one half of the vestibular face of the teeth the conventional adhesive procedure was carried out while in the other half was added an additional step with 5% NaOCl applied for 1 minute and washing after acid etchant. A resin post was adhered in each half and load was applied until fracture. The failure mode was evaluated and a SEM analysis was made. Posteriorly 10 samples of fluorotic and healthy ground enamel were used to measure the nanostructural characteristics by AFM (roughness average and absolute depth profile) and the VM in three operative steps (after ground, after etchant and after deproteinization). The Shapiro-Wilks and Brown-Forsythe methods were used to test the distribution of variables. The Paired Student's t-test was used to compare the differences between mean bond strength (MPa) in the two groups for SBS test. Chi-square analyzes were performed to compare the failure modes between groups. One-way ANOVA analysis and Tukey-Kramer post hoc test were used to compare groups for roughness average, absolute depth profile and Vickers microhardness. A greater SBS (32.17±4.20 MPa) and a surface more homogeneous and less contaminated were observed in the deproteinization subgruoup compared to the conventional...
Evaluar el efecto en la resistencia adhesiva al cizallamiento (SBS) de la aplicación de 5% de NAOCl después del grabado ácido en dientes anteriores fluoróticos tallados y analizar la superficie con microscopía electrónica de barrido (SEM), también comparar esmalte tallado fluorótico y sano por microscopía de fuerza atómica (AFM) y microdureza Vickers (VM). Para la prueba SBS 30 dientes anteriores con fluorosis moderada y severa de acuerdo al índice de Dean fueron seleccionados por un examinador previamente calibrado por un experto en fluorosis usando el coeficiente de correlación intraclase (ICC). La cara vestibular se preparó .3mm con la ayuda de una fresa calibrada para la preparación de carillas y una paralela con punta en chamfer de diamante a alta velocidad e irrigación. En una mitad de la superficie vestibular de los dientes se llevó a cabo el procedimiento adhesivo tradicional, mientras que en la otra mitad se incluyó un paso adicional con la aplicación de NaOCl al 5% por un minute y lavado posterior al grabado ácido. Un poste de resina fué adherido en cada mitad y se aplicó carga hasta la fractura. Se evaluó el modo de fallo y se realizó un análisis con SEM. Posteriormente se utilizaron 10 muestras de esmalte tallado fluorótico y sano para medir las características nanoestructurales por medio de AFM (rugosisdad promedio y perfil de profundidad absoluta) y la VM en tres diferentes pasos operativos (posterior al tallado, posterior al grabado ácido y posterior a la desproteinización). Se utilizaron los métodos de Shapiro Wilks y Brown-Forsythe para conocer la distribución de las variables. Una T de student pareada se utilizó para comparar la diferencia entre los promedios de la fuerza de unión (MPa) entre grupos para la prueba SBS. Se llevaron a cabo análisis de chi cuadrada para comparer los modos de fallo entre los grupos. Análisis de ANOVA de una vía y Turkey-Kramer post hoc fueron utilizados para comparar...
En revista Odóvtos, vol. 23, no.3 (septiembre-diciembre 2021)
Descripción basada en el contenido visto el 14 de noviembre, 2024
También disponible en formato HTML y EPUB